HOTS Question Analysis on E-Learning: a 21st Century Competency Evaluation - Ami Hibatul Jameel; Abd Gafur; Andy Sapta (Universitas Negeri Semarang, 2023)
The development in the 21st century brings changes in the education field. Universities, in this case, must also be able to produce graduates who are expected to be able to answer future challenges and be globally competitive. One way to succeed in 21st-century competencies and accommodate digital native learners is to integrate digital literacy and take advantage of assignments in the Universitas Terbuka e-learning. The questions on e-learning assignments should also raise students' critical thinking and creative thinking skills. However, do the existing tutorial assignments lead to higher order thinking skills (HOTS) or are they still at the level of lower thinking skills? This study aims to analyze tutorial assignments in UT e-learning to improve 21st-century competencies (critical thinking skills and creative thinking skills) among UT students, especially Educational Technology Study Program in the Faculty of Teacher Training and Educational Sciences. The research was conducted using a mixed method, qualitative and quantitative research approach. Data was collected by using the document analysis technique which was then processed and analyzed qualitatively and quantitatively. After doing the analysis, the research results show that the tutorial assignments have yet to lead to the higher order thinking skills (HOTS). This result leads to the recommendation that the learning experience should become ownership for the students so that students could be more attached and eager to learn and do the assignments.